Association of Survival With Shorter Time to Radiation Therapy After Surgery for US Patients With Head and Neck Cancer - Harris, Jeremy P. (JAMA Otolaryngol Head Neck Surg, 2018)
IMPORTANCE: Shortening the time from surgery to the start of radiation (T(S-RT)) is a consideration for physicians and patients. Although the National Comprehensive Cancer Network recommends radiation to start within 6 weeks, a survival benefit with this metric remains controversial. OBJECTIVE: To determine the association of delayed T(S-RT) with overall survival (OS) using a large cancer registry. DESIGN, SETTING, AND PARTICIPANTS: In this observational cohort study, 25 216 patients with nonmetastatic stages III to IV head and neck cancer were identified from the National Cancer Database (NCDB). EXPOSURES: Patients received definitive surgery followed by adjuvant radiation therapy, with an interval duration defined as T(S-RT). MAIN OUTCOMES AND MEASURES: Overall survival as a function of T(S-RT) and the effect of clinicopathologic risk factors and accelerated fractionation. RESULTS: We identified 25 216 patients with nonmetastatic squamous cell carcinoma of the head and neck. There were 18 968 (75%) men and 6248 (25%) women and the mean (SD) age of the cohort was 59 (10.9) years. Of the 25 216 patients, 9765 (39%) had a 42-days or less T(S-RT) and 4735 (19%) had a 43- to 49-day T(S-RT). Median OS was 10.5 years (95% CI, 10.0-11.1 years) for patients with a 42-days or less T(S-RT), 8.2 years (95% CI, 7.4-8.6 years; absolute difference, −2.4 years, 95% CI, −1.5 to −3.2 years) for patients with a 43- to 49-day T(S-RT), and 6.5 years (95% CI, 6.1-6.8 years; absolute difference, −4.1 years, 95% CI, −3.4 to −4.7 years) for those with a 50-days or more T(S-RT). Multivariable analysis found that compared with a 42-days or less T(S-RT), there was not a significant increase in mortality with a 43- to 49-day T(S-RT) (HR, 0.98; 95% CI, 0.93-1.04), although there was for a T(S-RT) of 50 days or more (HR, 1.07; 95% CI, 1.02-1.12). A significant interaction was identified between T(S-RT) and disease site. Subgroup effect modeling found that a delayed T(S-RT) of 7 days resulted in significantly worse OS for patients with tonsil tumors (HR, 1.22; 95% CI, 1.05-1.43) though not other tumor subtypes. Accelerated fractionation of 5.2 fractions or more per week was associated with improved survival (HR, 0.93; 95% CI, 0.87-0.99) compared with standard fractionation. CONCLUSIONS AND RELEVANCE: Delayed T(S-RT) of 50 days or more was associated with worse overall survival. The multidisciplinary care team should focus on shortening T(S-RT) to improve survival. Unavoidable delays may be an indication for accelerated fractionation or other dose intensification strategies.